2010
DOI: 10.1007/s11284-010-0709-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of subpopulations of North American elk (Cervus elaphusL.) using multiple lines of evidence: habitat use, dietary choice, and fecal stable isotopes

Abstract: We used multiple lines of evidence to assess habitat selection, dietary choice, and nutritional outcomes for a population of North American elk (Cervus elaphus), confined to a relatively small and isolated landscape of public and private land in south-central Great Plains, USA. The area of suitable elk habitat was a topographically diverse matrix of mature oak savannah, C 4 -dominated grasslands, and C 3 -dominated agricultural fields surrounded by unsuitable lowlands fragmented by anthropogenic activities. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…We would have overlooked this variation in habitat selection strategies, had we relied solely on a pooled RSF and not investigated individual behaviour. The variation that we uncovered in individual behaviour may indicate subpopulation structure, similar to that found in caribou Rangifer tarandus (Nagy et al 2011), Yellowstone bison (Olexa andGogan 2007, Halbert et al 2012) and elk Cervus canadensis (Walter et al 2010). However, we did not have data adequate to detect subpopulation structure, which may be defined by spatial distribution, social interaction, diet and habitat selection.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We would have overlooked this variation in habitat selection strategies, had we relied solely on a pooled RSF and not investigated individual behaviour. The variation that we uncovered in individual behaviour may indicate subpopulation structure, similar to that found in caribou Rangifer tarandus (Nagy et al 2011), Yellowstone bison (Olexa andGogan 2007, Halbert et al 2012) and elk Cervus canadensis (Walter et al 2010). However, we did not have data adequate to detect subpopulation structure, which may be defined by spatial distribution, social interaction, diet and habitat selection.…”
Section: Discussionsupporting
confidence: 77%
“…However, we did not have data adequate to detect subpopulation structure, which may be defined by spatial distribution, social interaction, diet and habitat selection. In the future, detection of subpopulation structure could be aided by analysis of a larger number of collared bison with simultaneously active collars (Nagy et al 2011), as well as dietary and genetic data (Walter et al 2010, Halbert et al 2012). Regardless, similar to other studies (Gillingham and Parker 2008, Nielsen et al 2009, Anderson and Johnson 2014), our analyses broadly demonstrate how habitat models estimated by pooling data from multiple animals may conceal individual behaviour, which may have implications for management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…[28] With few exceptions, [53] feces from large herbivores have higher δ 15 N values than the diet (approx. 3-4‰ [6,7,10,22,23,27,51,54,55] ) with marked variation in the discrimination within and among species. [23] For captive northern ungulates in this study on formulated diets, estimates of fecal fiber-diet discrimination factors from the detergent-free fiber assay were similar to those observed in other ungulates: fecal fibers of reindeer/caribou and muskoxen had consistently higher values (3.6 ± 1.4‰ and 2.8 ± 0.5‰, respectively) over a range of dietary δ 15 N values.…”
Section: Discussionmentioning
confidence: 99%
“…Stable nitrogen isotope ratios (δ 15 N values) in excreta have been used to assess diets in primates, [1,2] black bears (Ursus americanus), [3] several African ungulates, [4,5] muskoxen (Ovibos moschatus), [6] elk (Cervus elaphus), [7] and small mammals. [8] Changes in δ 15 N values have also been used to evaluate trophic and ecological relationships in large mammalian predator-prey systems, [9] wild and domestic herbivores, [10][11][12] rodents, [13] grazing waterfowl, [14] and seabirds; [15] as well as the nutritional status in northern ungulates, [16][17][18] orangutans (Pongo pygmaeus), [19] and reptiles.…”
mentioning
confidence: 99%
“…We summarise several applications below to highlight the types of spatial questions that can be addressed. Walter et al (2010) found that by combining faecal δ 13 C, δ 15 N and %N values with faecal microhistology, radiotelemetry, and observational data it was possible to track differences in habitat and resource use (including consumption of cultivated crops) by North American elk. Conversely, The prospects of poop Gustine et al (2012) found that faecal δ 15 N values were not particularly well suited for distinguishing populations of caribou (Rangifer tarandus) in Alaska.…”
Section: Applications Of C and N Isotopes In Faecesmentioning
confidence: 99%